"Sedition" and "seditious tendency" within Malaysian Sedition Act 1948: a comparative study between Malaysia and India / Diba Natalia Ishak ... [et al.] - Abd Jalil, Asiah; Ishak, Diba Natalia; Hairudin, Haifaa 'Atiqa; Abdul Ghafar, Syafiqah (2011)
The basis of this research is to compare the law of seditions between Malaysia and India. Comparative study for the purpose of this research would focus not only on the differences, but also the similarities of the offence of sedition in both countries. This research is centered on the interpretation of the words "sedition" and "seditious tendency" in Malaysia and India, as well as to study the requirement of intention under the offence of sedition. By looking at these two elements, this research is to analyze the relevancy of sedition laws in the modern 21st century. The technique we adopted was the qualitative research methodology, which consists of literature research namely library literature search and Internet research. There were also personal interviews with experts on the topics that had been incorporated in the research finding. It was discovered that in both countries the laws are identical in terms of reasons for enactment and the interpretation of the sedition offence. The research findings indicated that the differences could be seen on the incorporation of offence of sedition and the punishment for the offence. In Malaysia the offence of sedition is provided under a separate statute that is the Malaysian Sedition Act 1948 where it stands alone. Contrary to India, the offence was incorporated in the Indian Penal Code by virtue of Article 124A. The difference is also in terms of the degree of punishment, where higher degree of punishment is imposed in India. It had been suggested that the offence of sedition in both countries should not be repealed completely but to be amended to a certain extent in order to balance the interests between public and government.